2000
DOI: 10.1093/intimm/12.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Serrate1-induced Notch signalling regulates the decision between immunity and tolerance made by peripheral CD4+ T cells

Abstract: Signals derived from antigen-presenting cells (APC) influence the functional differentiation of CD4(+) T cells. We report here that Serrate1 (Jagged1), a ligand for the Notch1 receptor, may contribute to the differentiation of peripheral CD4(+) T cells into either helper or regulatory cells. Our findings demonstrate that antigen presented by murine APC overexpressing human Serrate1 induces naive peripheral CD4(+) T cells to become regulatory cells. These cells can inhibit primary and secondary immune responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
135
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(144 citation statements)
references
References 52 publications
5
135
4
Order By: Relevance
“…In addition, in a recent study it was shown that interactions between DCs and T cells are bi-directional under conditions of cell activation (48). It is not clear, however, whether the Notch signal in the DC to T cell direction is suppressive; while in one study it was shown that APCs that overexpress Notch ligand have suppressive qualities, in another study it was shown under more physiologic conditions that inhibition of Notch signaling led to decreased cytokine production (IFN-␥) by interacting T cells (48,51). Thus, while we recognize that mature DCs can be directly tolerogenic, there is no convincing evidence that the latter involves the Notch pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a recent study it was shown that interactions between DCs and T cells are bi-directional under conditions of cell activation (48). It is not clear, however, whether the Notch signal in the DC to T cell direction is suppressive; while in one study it was shown that APCs that overexpress Notch ligand have suppressive qualities, in another study it was shown under more physiologic conditions that inhibition of Notch signaling led to decreased cytokine production (IFN-␥) by interacting T cells (48,51). Thus, while we recognize that mature DCs can be directly tolerogenic, there is no convincing evidence that the latter involves the Notch pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been previously shown that activation of Notch signaling, by overexpressing the specific Notch ligand Jagged/Serrate1 in APCs, in peripheral murine T cells results in the differentiation of Ag-specific CD4 ϩ lymphocytes into T-reg cells, which can transfer tolerance to naive mice (30). Conversely, Ag-dependent T cell activation has been shown to trigger the activation of the Notch signaling pathway, since stimulation of purified murine CD4 ϩ T cells with anti-CD3 and anti-CD28 Abs has been shown to induce a transient increase in Notch ligand and receptor expression and the concomitant addition of IL-10 further increases the transcription of Notch ligand genes (31).…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ induces FOXP3 expression in peripheral naive T cells, allowing their differentiation into peripherally induced T Reg cells 62,94 . A role for Notch signalling in peripherally induced T Reg cell differentiation was first suggested by several experiments showing that overexpression of the Notch ligand Jagged 1 on APCs led to peripherally induced T Reg cell differentiation both in vitro and in vivo 95,96 . The peripheral induction of T Reg cells by Notch signalling was shown to involve the activation of FOXP3, the master transcription factor of T Reg cells.…”
Section: Notch and Regulatory T Cell Functionsmentioning
confidence: 99%